An in silico approach to understand the structure–function properties of a serine protease (Bacifrinase) from Bacillus cereus and experimental evidence to support the interaction of Bacifrinase with fibrinogen and thrombin. Issue 3 (17th February 2017) - Bora, Bandana; Biswas, Akash Deep; Gurung, Arun Bahadur; Bhattacharjee, Atanu; Mattaparthi, Venkata Satish Kumar; Mukherjee, Ashis K.
Abstract : Microbial fibrinogenolytic serine proteases find therapeutic applications in the treatment of thrombosis- and hyperfibrinogenemia-associated disorders. However, analysis of structure–function properties of an enzyme is utmost important before its commercial application. In this study, an attempt has been made to understand the structure of a fibrinogenolytic protease enzyme, "Bacifrinase" from Bacillus cereus strain AB01. From the molecular dynamics trajectory analysis, the modelled three-dimensional structure of the protease was found to be stable and the presence of a catalytic triad made up of Asp102, His83 and Ser195 suggests that it is a serine protease. To understand the mechanism of enzyme–substrate and enzyme–inhibitor interactions, the equilibrated protein was docked with human fibrinogen (the physiological substrate of this enzyme), human thrombin and with ten selective protease inhibitors. The Bacifrinase–chymostatin interaction was the strongest among the selected protease inhibitors. The serine protease inhibitor phenyl methane sulphonyl fluoride was found to interact with the Ser134 residue of Bacifrinase. Furthermore, protein–protein docking study revealed the fibrinogenolytic property of Bacifrinase and its interaction with Aα-, Bβ- and Cγ-chains human fibrinogen to a different extent. However, biochemical analysis showed that Bacifrinase did not hydrolyse the γ-chain of fibrinogen. The in silico and spectrofluorometric studies also showed interaction of Bacifrinase with thrombin as well as fibrinogen with a Kd value of 16.5 and .81 nM, respectively. Our findings have shed light on the salient structural features of Bacifrinase and confirm that it is a fibrinogenolytic serine protease.